Vibrio natriegens as a pET-Compatible Expression Host Complementary to Escherichia coli - Xu, Jiaqi; Dong, Feng; Wu, Meixian; Tao, Rongsheng; Yang, Junjie; Wu, Mianbin; Jiang, Yu; Yang, Sheng; Yang, Lirong (Frontiers in Microbiology, 2021)
Efficient and novel recombinant protein expression system can further reduce the production cost of enzymes. Vibrio natriegens is the fastest growing free-living bacterium with a doubling time of less than 10 min, which makes it highly attractive as a protein expression host. Here, 196 pET plasmids with different gene of interest (GOI) were electroporated into the V. natriegens strain VnDX, which carries an integrated T7 RNA polymerase expression cassette. 65% and 75% of the tested GOI obtained soluble expression in V. natriegens and E. coli, respectively, 20 GOI of which showed better expression in the former. Furthermore, we have adapted a consensus ‘what to try first’ protocol for V. natriegens based on Terrific Broth medium. 6 sampled GOI encoding biocatalysts enzymes thus achieved 50% to 128% higher catalytic efficiency under the optimized expression conditions. Our study demonstrated V. natriegens as a pET compatible expression host with a spectrum of highly expressed GOI distinct from E. coli and an easy-to-use consensus protocol, solving the problem that some GOI can't be expressed well in E. coli.